A Case of Diffuse Cutaneous Leishmaniasis in a HIV Positive Patient - Patwary, I; Rahman, M; Ahmed, M; Ahmedm, S; Choudhury, MSR (Journal of Bangladesh College of Physicians and Surgeons, 2011)
A cultivator of 30 years of age presented with fever, cough, diarrhoea, anorexia and weight loss for 6 months and papulonodular skin lesions for one month. Skin lesions appeared on the face, first over the left cheek and gradually involved whole of his face, extremities and external genitalia sparing the trunk. Skin biopsy from the nodule showed collection of histiocytes, lymphocytes & plasma cells with plenty of LD bodies inside the histiocytes. Screening test for HIV was positive and it was confirmed with western blot. Probably this is the first case Leishmaniasis/ HIV co infection reported from Bangladesh. DOI: http://dx.doi.org/10.3329/jbcps.v29i2.7957 (J Bangladesh Coll Phys Surg 2011; 29: 106-108)